Return Migration of Foreign Students - Govert E. Bijwaard; Qi Wang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Using administrative panel data, this paper presents a comprehensive empirical analysis of the return of recent foreign students in the Netherlands. We focus on how individual labour market changes and marriage formation influence their decision to leave. Our model allows for correlated unobserved heterogeneity across the migration, the labour market and the marriage formation processes. The large size of the data permits us to stratify the analysis by five groups based on the country of birth. The empirical analyses reveal that employment hardly affects return behaviour of students and unemployment induces them to leave. Marriage in the Netherlands makes the students more prone to stay. The size of the impact of these life course experiences on return differs by income, age at entry, business cycle and gender.
Keywords: F22; J64; J12; C41; 330; student migration; correlated hazards; labour dynamics; marriage formation; return migration